STRATEGI PENDEKATAN KONSELING BEHAVIORAL UNTUK MENINGKATKAN MINAT BELAJAR KEAGAMAAN PADA REMAJA DI MESJID TAQWA MUHAMMADIYAH - Indraji, Muhammad Iqbal; Kustiawan, Winda (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2024)
This research aims to determine the application of behavioural counselling guidance in increasing adolescents' interest in learning. This research uses descriptive qualitative methods. The research location was at the Taqwa Muhammadiyah Tebing Tinggi mosque from 4-12 July 2023. There are 2 data sources, namely primary and secondary. informants 4 teenagers and 1 counsellor. Data collection techniques in the form of observation, interviews and documentation. Data analysis Data reduction, data display, data verification or conclusions. Tekhnik kreadibilitas or absahan data using trangulation in the form of time, sources and techniques. the results of Bk's research there are 4 adolescents have an interest in learning at school this is seen that adolescents when learning like to be sleepy, fall asleep, do not do assignments and do not go to school without information, the causes that affect adolescents' interest in learning are due to less interesting subjects, addicted to online games, do not understand the lessons learned besides that it is also due to lack of motivation in learning, The application of behavioural counselling conducted by the location at the Taqwa Muhammadiyah mosque is carried out with individual counselling through 5 stages, namely: assemen, goal setting, Implementation technique, Evaluation termination and Feedback.